Systematic Literature Review: Role Effectiveness, Challenges, and Empowerment of Millennial Leaders - Chlarita Ekklesia Putrihadi; Nuri Herachwati (Jurnal Ilmiah Sumber Daya Manusia, 2023)
The millennial workforce has a large proportion in 2022 and is expected to continue to increase in the coming year in corporate settings. It is predicted that by 2025, the millennial workforce will reach 75% of the total workforce (Ernst & Young, 2015). In several studies conducted, millennials are currently not only studied as employees, but also as leaders in a company. Many of the leadership transitions have been handed over to millennial generation employees who are considered more productive and have the potential to lead. Seeing this phenomenon, companies need to consider how the development program should be given to prospective future leaders, so that they can improve their quality and be ready to lead a team. Therefore, researchers will explore previous research studies in order to obtain a stronger theoretical foundation for millennial leaders. By applying the systematic literature review method, this study aims to determine the roles and challenges faced by millennial leaders, as well as the empowerment programs needed to prepare millennials to become leaders. The review process begins with the collection of 616 articles from the Scopus database, where in the final stage there are 34 journals that will go through a further analysis process. The results show that the role and challenges of millennials in leading the face of difficult situations and conditions. Communication skills and openness in the learning process are needed. Providing the right mentoring and self-development programs will improve the leadership quality in millennials (Adiawaty, 2019).